Pengembangan Tanaman Sereh Wangi untuk Bioreklamasi Lahan dan Pemberdayaan Ekonomi Masyarakat di Muaro Jambi - Mursalin Mursalin; Eva Achmad; Ardi Novra (Agrokreatif: Jurnal Ilmiah Pengabdian kepada Masyarakat, 2020)
Degraded land due to brick industry, piling material, and coal mining activities are widely covered the area of Kebon IX Village, Sungai Gelam Subdistrict, Muaro Jambi District. This service activity was aimed at encouraging collective action by the village community of Kebun IX to apply citronella cultivation and processing technology in order to rehabilitate their land as well as develop productive economic businesses as a substitute for their old businesses that were not environmentally friendly. The method used was the combination of Participatory Rural Appraisal (PRA) and collective action model in promotion strategy and technology adoption. Through counseling, training and demonstration plots, four types of integrated businesses, including cultivation, processing and utilization of citronella by-product, have been successfully developed in Kebon IX Village. Citronella plants at aged 6‒8 months produced leaves at a price of IDR 500/kg and after 3 months can be harvested again. One clump of citronella plants can produce 1.5 kg at the first harvest and increase to 2.0 kg after the next harvest. One hectare of land can contain 1000‒1500 clumps of citronella plants. Citronella plant soil costs IDR 250,000/L, the residue of the distillation can be used as animal feed (IDR 150/kg) or used as trichocompost (IDR 1,200/kg). Trichocompost is also needed as organic fertilizer for the continuity of citronella cultivation. The integration of citronella plants cultivation and processing industry has a positive impact on land reclamation efforts as well as to empower the community's economy.